PRODUCTIVITY AND ECONOMIC IMPACT OF BAMBOO IN MONOCULTURE VERSUS MIXED SYSTEMS: IMPLICATIONS FOR SOCIAL FORESTRY - Ghoitsa Rohmah Nurazizah; Siti Badriyah Rushayati; Hardjanto; Herry Purnomo; Nyoto Santoso (Association of Indonesian Forestry and Environment Researchers and Technicians, 2026)
Bamboo forests serve as valuable assets which assist in developing social forestry programs that benefit local communities. The research investigates how bamboo grows and its economic value through two different planting methods which include monoculture and mixed systems at a Indonesian village forest. Researchers used systematic sampling methods to collect data from 21 plots which included 14 monoculture plots 6 mixed-system plots and 1 shrub plot. The research team focused on gathering data about clump characteristics and culm density and regeneration proportion. The researchers used the Mann–Whitney U test to analyze system differences because the data did not follow normal distribution. The study results show that monoculture bamboo systems produce higher output levels and generate greater financial benefits than mixed systems. The monoculture stands achieved an annual output of 6,374 culms per hectare which results in an estimated economic value of IDR 50,992,000 per hectare every year. The mixed systems produced 5,242 culms per hectare each year whereas the system generated an output of 5,242 culms. The study found that monoculture systems produced more young bamboo regeneration which reached 30.8% compared to mixed systems which generated 27.0% of young bamboo regeneration showing that monoculture systems have better regenerative capabilities.